STUDI HABITAT DAN JENIS PAKAN BADAK SUMATERA (DICERORHINUS SUMATRENSIS) DI KUTAI BARAT DAN MAHAKAM ULU KALIMANTAN TIMUR - Muslim, Ahmad; Nurdjali, Bachrun; Dewantara, Iswan (Universitas Tanjungpura, 2015)
The Sumatran rhinos (Dicerorhinus sumatrensis) is the smallest and be the most primitive of the five species of rhinoceros that still alive. In the 1990s the status of the Sumatran rhinos population in East Kalimantan never again recorded scientifically (Meijaard, 1996). In 2013 a team of WWF-Indonesia Kutai Barat find any sign of the rhinos that is supported by the findings of the trail and a video camera recording automatically. The study aims is to determine the type of vegetation as a feed resources in the trajectory path and to determine the condition of the Sumatran rhinos habitat (Dicerorhinus sumatrensis) in Kutai West and East Kalimantan's Mahakam Ulu. This study used a double plot irregularly conducted by purposive. The results to showed level of habitat suitability between zone 1 and zone 3 has a composition of the same type, that is 70.270% with 48 types of vegetation found in which 32 species a feed of Sumatran Rhinos (Dicerorhinus sumatrensis). Keywords :Feed, habitat, Sumatran rhino ( Dicerorhinus sumatrensis ).